2006
DOI: 10.5713/ajas.2006.526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ensiling Alfalfa with Whole-crop Maize on the Chemical Composition and Nutritive Value of Silage Mixtures

Abstract: The aim of this study was to evaluate the chemical composition, in vitro DM degradability, ME and OMD of alfalfamaize silage mixtures in comparison to pure maize and alfalfa silages, and to test the existence of associative effects of ensiling alfalfa forage with whole-crop maize using the in vitro gas production technique. Ensiling alfalfa with whole-crop maize had a significant (p<0.001) effect on chemical composition, pH, in vitro DM degradability, OMD and estimated ME values of mixtures. DM content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
(36 reference statements)
4
23
2
3
Order By: Relevance
“…Water soluble carbohydrates content in corn was higher compared to alfalfa. A higher ratio of corn enhanced the fermentation characteristics of alfalfa-corn mixed silage without any treatment, with a lower pH value, higher LA content and lower NH 3 -N level at this experiment (Table 2); low pH value can be explained by a higher content of carbohydrates and lower concentration of buffering capacity with a higher corn ratio in forages mixture and was in agreement with results by Ozturk et al (2006); NH 3 -N contents with all treatments increased as alfalfa ratio increased in forages mixture perhaps because more proteolysis occurs and results in higher NH 3 -N level with a higher ratio of alfalfa. Similarly, addition of gramineous plants resulted in a lower pH value, higher LA content and lower NH 3 -N concentration (Muck 1988;Heron et al 1989;Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Water soluble carbohydrates content in corn was higher compared to alfalfa. A higher ratio of corn enhanced the fermentation characteristics of alfalfa-corn mixed silage without any treatment, with a lower pH value, higher LA content and lower NH 3 -N level at this experiment (Table 2); low pH value can be explained by a higher content of carbohydrates and lower concentration of buffering capacity with a higher corn ratio in forages mixture and was in agreement with results by Ozturk et al (2006); NH 3 -N contents with all treatments increased as alfalfa ratio increased in forages mixture perhaps because more proteolysis occurs and results in higher NH 3 -N level with a higher ratio of alfalfa. Similarly, addition of gramineous plants resulted in a lower pH value, higher LA content and lower NH 3 -N concentration (Muck 1988;Heron et al 1989;Zhang et al 2015).…”
Section: Discussionsupporting
confidence: 81%
“…Alfalfa had a higher content of CP compared to corn due to nitrogen fixation from atmosphere (Ozturk et al 2006;Amer et al 2012). As a result, an increase in alfalfa proportion resulted in a higher concentration of CP in aflafla-corn mixed silage reflected in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associative effects were observed on the OM digestibility and NDFD with a mixture of corn and lucerne silages in vitro (Moss et al, 1992). This observation was also made when both forages were simultaneously ensiled (Ozturk et al, 2006). This effect could be explained by the buffering ability of lucerne which could minimise the decrease of ruminal pH due to the fermentation of corn starch, thus stimulating cellulolytic activity (Moss et al, 1992).…”
Section: Associative Effects Between Temperate Grasses and Legumesmentioning
confidence: 71%
“…These volatile substances are known as bio-flavor compounds. Indeed, DM of silage has also associated with Fleigh points (Ozturk et al, 2006). Other study reported that moisture content of silage affects microbial activity during ensilage (Weinberg and Muck, 1996).…”
Section: Palatability Of Silagementioning
confidence: 99%
“…Fleigh points (Fp) was calculated according to Kiliç (1984) as previously reported by Ozturk et al (2006) …”
Section: Measurement Of Ph Fleigh Points and Lactic Acid Concentrationmentioning
confidence: 99%